Next-generation sequencing with comprehensive bioinformatics analysis facilitates somatic mosaic APC gene mutation detection in patients with familial adenomatous polyposis - Borahm Kim; Dongju Won; Mi Jang; Hoguen Kim; Jong Rak Choi; Tae Il Kim; Seung-Tae Lee (BMC, 2019)
Abstract Background Familial adenomatous polyposis (FAP) is an autosomal dominant colorectal tumor characterized by numerous adenomatous colonic polyps that often lead to colon cancer. Although most patients with FAP harbored germline mutations in APC gene, it was recently recognized that patients with clinical FAP, but without detectable pathogenic mutations, could be associated with somatic mosaic APC mutation. Methods We reanalyzed the nest-generation sequencing (NGS) gene panel testing results of patients who were diagnosed with FAP, but did not have APC mutations, at Yonsei Cancer Prevention Center between July 2016 and March 2018. We tested several variant calling algorithms to identify low level mosaic variants. In one patient with a low frequency APC mutation, NGS analysis was performed together with endoscopic biopsy. Variant calling tools HaplotypeCaller, MuTect2, VarScan2, and Pindel were used. We also used 3'-Modified Oligonucleotides (MEMO)-PCR or conventional PCR for confirmation. Results Among 28 patients with clinical suspicion of FAP but no detectable pathogenic variants of colonic polyposis associated genes, somatic mosaic pathogenic variants were identified in seven patients. The variant allele frequency ranged from 0.3 to 7.7%. These variants were mostly detected through variant caller MuTect2 and Pindel, and were further confirmed using mutant enrichment with MEMO-PCR. Conclusions The NGS with an adequate combination of bioinformatics tools is effective to detect low level somatic variants in a single assay. Because mosaic APC mutations are more frequent than previously thought, the presence of mosaic mutations must be considered when analyzing genetic tests of patients with FAP.